2009
DOI: 10.3399/bjgp09x420329
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of outcome in patients presenting with fatigue in primary care

Abstract: Although fatigue is a common problem presenting to primary care, few prospective studies have examined the contribution of a wide range of prognostic factors. AimTo determine the combination of factors most strongly associated with a favourable or unfavourable course of fatigue, when fatigue is presented as a main symptom in primary care. Design of studyProspective, observational cohort study with a 1-year follow-up. SettingA total of 147 primary care practices in the Netherlands. MethodPatients presenting wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…Substantial fatigue is also a predictor of chronic fatigue and CFS [50,51]. Although a lack of CFS screening in the study makes us unable to rule out already existent CFS, the reported substantial fatigue could still represent a risk factor, indicating a need for fatigue screening at an early stage of CLBP.…”
Section: Discussionmentioning
confidence: 86%
“…Substantial fatigue is also a predictor of chronic fatigue and CFS [50,51]. Although a lack of CFS screening in the study makes us unable to rule out already existent CFS, the reported substantial fatigue could still represent a risk factor, indicating a need for fatigue screening at an early stage of CLBP.…”
Section: Discussionmentioning
confidence: 86%
“…Anxiety, depression and catastrophising beliefs about pain have been shown to be associated with the presence of chronic pain and with a poor prognosis in people with various pain conditions. [14][15][16][17] The temporal relationship between chronic pain and mental health remains unclear, and it is likely that there is a 'bi-directional aetiology' 18 -pain causing poor mental health and vice versa. In depressed patients, neuroimaging has provided evidence of disturbed prefrontal brain activity and a dysfunction of emotion regulation during experimental pain stimulation.…”
Section: Modifiable Factors Associated With Painmentioning
confidence: 99%
“…Kant et al (2003) proposed an epidemiological framework for the etiology of prolonged fatigue, consisting of individual variables (e.g., health status, life style, coping), private circumstances (e.g., domestic and social factors), and work characteristics (e.g., work content, working conditions, and work relations). High fatigue severity and, to a lesser extent, poor mental health, physical and psychological attributions, and expectations about chronicity have been associated with prolonged fatigue (Nijrolder, van der Horst, & van der Windt, 2008;Nijrolder, van der Windt, & van der Horst, 2009). Loge, Ekeberg, and Kaasa (1998) reported that 22% of Norwegians aged 19-80 years experienced prolonged fatigue.…”
mentioning
confidence: 99%